Profiles of prostaglandin F2α metabolite in dairy cattle during luteal regression and pregnancy: implications for corpus luteum maintenance†. Issue 1 (8th May 2019) - Mezera, Megan A; Hamm, Caleb S; Gamarra, Caio A; Gennari, Rodrigo S; Prata, Alexandre B; Sartori, Roberto; Wiltbank, Milo C
Abstract: Mechanisms of bovine corpus luteum (CL) maintenance during the second month of pregnancy have not been adequately investigated, despite significant reproductive losses. In the first month, interferon-tau is believed to suppress oxytocin-stimulated prostaglandin F2α (PGF) production, yet there are conflicting reports of circulating PGF metabolite (PGFM). In this study, characterization of PGFM and P4 occurred through continuous bihourly blood sampling in cows undergoing CL regression (day 18–21, n = 5), and during the first (day 18–21, n = 5) and second month (day 47–61; n = 16) of pregnancy. Cattle in the second month were assigned to control (n = 8) or oxytocin treatment (n = 8; three pulses to mimic luteolysis) to evaluate if oxytocin receptors were active. All cows but one (which had elevated PGFM prior to oxytocin treatment) maintained the pregnancy. Basal PGFM concentrations were low (11.6 ± 0.7 pg/mL) in the first month but increased 2.54-fold in the second month. Few (0.26 ± 0.12 pulses/day) PGFM pulses with low peak concentrations (28.8 ± 3.1 pg/mL) were observed during the first month of pregnancy, similar to cows not undergoing regression. However, in the second month, frequency (1.10 ± 0.26 pulses/day) and peak concentration (67.2 ± 5.0 pg/mL) of PGFM pulses increased, displaying similar frequency but lower peak PGFM than seen in regression (1.44 ± 0.14 pulses/day; 134.5 ± 18.9 pg/mL). Oxytocin treatment increased likelihood of PGFM pulses post-treatment and increased peak concentration (89.7 ± 10.1 pg/mL) in cows during the second month. Thus, cows have more PGFM pulses during second than first month of pregnancy, possibly induced by endogenous oxytocin, indicating suppression of PGF production is an important mechanism for CL maintenance during first but not second month of pregnancy. Abstract : Low basal PGFM concentration and minimal pulsatile activity are observed in first month of pregnancy before increasing during second month of pregnancy, suggesting different mechanisms maintain the CL in the first vs second month of pregnancy.